How do you change y - 2/3 = -2(x - 1/4)y23=2(x14) into slope intercept form?

1 Answer
Feb 26, 2017

Slope-intercept form is y = mx+cy=mx+c

y = -2x+1 1/6" or " y = -2x+7/6y=2x+116 or y=2x+76

Explanation:

y - 2/3 = -2(x-1/4)y23=2(x14)

Follow the usual process of simplifying - start by getting rid of the brackets.

y - 2/3 = -2x+1/2y23=2x+12

Slope-intercept form is " "y = mx +c" " y=mx+c so isolate the yy-term

y= -2x+1/2+2/3" "larry=2x+12+23 add the fractions

y = -2x +(3+4)/6y=2x+3+46

y = -2x+7/6" or " y = -2x+1 1/6y=2x+76 or y=2x+116